Neurosyphilis cerebrospinal fluid findings in patients with ocular syphilis. (2nd January 2021) - Bazewicz, M.; Lhoir, S.; Makhoul, D.; Libois, A.; Van den Wijngaert, S.; Caspers, L.; Willermain, F.
ABSTRACT: Purpose : To evaluate neurosyphilis cerebrospinal fluid (CSF) findings and initial ophthalmic manifestations in patients with syphilitic uveitis. Methods : We retrospectively reviewed the records of CSF analysis of 14 patients with syphilitic uveitis with treponemal analysis - chemiluminescent immunoassay and TPHA- and non-treponemal analysis - Rapid Plasma Reagin test – RPR. Results : 86% were males and 43% HIV+. Ocular signs of syphilis lead to the diagnosis of syphilis in 78% of patients. Typical syphilitic uveitis presentations included: acute syphilitic posterior placoid chorioretinitis (50% of patients), retinitis (21% of patients) and punctate inner retinitis (7% of patients). 57% of patients had definite neurosyphilis by the CDC criteria, while 71% had CSF abnormalities suggestive of central nervous system involvement. Conclusion : Based on international guidelines, the frequent CSF abnormalities found in syphilitic uveitis patient supports the diagnosis of neurosyphilis in a majority of patients.